The dialectic of the relationship betweenthe aesthetic and the ethical - عبد الرحيم, ياسر (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The problem of the relationship between beauty and ethics in the field of aesthetic thinking represents the deepest and most complex problems, and it explains the conflicting opinions and different statements we see about this relationship, and the schools and trends that have emerged from it that have reached the point of contradiction and dissonance. This research seeks to try to understand and clarify this problem, as there are two trends struggling in the dialectic of the relationship between the aesthetic and the ethical. The first: represents Absolute Moralizing and the second: represents Aestheticism. The first current asserts that art is a subject of aesthetic judgment because beauty represents a special type of moral goodness, while the second current believes that moral judgments have absolutely no relation to art, and between these two currents there is A movement that takes a position of mediation or reconciliation between them. Keywords: (beauty, ethics, goodness, aesthetics, art for art’s sake, aesthetic thought, aesthetic schools)ـ